Pengaruh Produk Dan Pelayanan Terhadap Keputusan Anggota Menggunakan Jasa BMT ( Baitul Maal Wa Tamwil ) Bina Insan Sejahtera Di Kota Jambi - Darmiwati Darmiwati; Arsa Arsa; Mohammad Orinaldi (Jurnal of Management and Social Sciences, 2023)
The method used by the authors in this study is a quantitative method, based on the results of the influence of products and services on members' decisions to use the services of Baitul Maal Wa Tamwil Bina Insan Prosperous City of Jambi. The results of the research on social class variable test, product quality and purchasing decisions were declared valid. Testing the hypothesis for the product variable (X1) 0.259 has an impact on members' decisions seen from the t value of 1.877 and a significant 0.00. It was concluded that Ho was rejected while H1 was accepted. Testing the hypothesis for service variables (X2) 0.329 service influences member decisions. Judging from the statistical value of t count of 2.437 and a significant 0.00 it is concluded that Ho is rejected while H2 is accepted. (F test) to get the result that the independent variables namely products and services jointly influence the dependent variable (member decision). This can be seen from the results obtained F count 2.925 with a significant price of 0.043.